An exploratory study of addressing bias for child abuse teams: the role of narrative medicine - Brown, Jocelyn; Cornelius, Talea; Farland, Gabriella; Gialopsos, Philip; Charon, Rita (Frontiers in Pediatrics, 2026)
IntroductionArt and humanities-based approaches have been incorporated in Diversity, Equity and Inclusion (DEI) training and anti-bias curriculum to address structural racism and personal biases via reflection. Research has shown that the use of visual art or texts via narrative medicine workshops results in improved communication with patients and colleagues and increased commitment to interrupting bias.MethodsUsing members of a hospital-based Child Abuse Bias Mitigating Task Force, this study tests the hypothesis that narrative medicine workshops provide a space where conversations of race and bias in the context of child abuse evaluations can take place.ResultsWorkshops participants noted the unique group experience that, through sharing and communal support, helped build compassion, function more effectively as a team, and even find confidence in their own voice. Intertwined with the ability to connect with and support each other as a team was the common thread of understanding differences in perspectives and personal histories. Most participants agree that the workshops increased their ease in having conversations about privilege and bias in clinical assessment.ConclusionWe conclude that the use of art and creativity allows for personal and structural insights on racism and social advocacy with significant promise for reducing bias in child abuse evaluations.